From Globalisation to Glocalisation: A Study Case from Galengdowo, Jombang - Suksmawati, Herlina; Kusuma, Ade; Hapsari, Renitha Dwi; Firdaus, Praja (Nusantara Science and Technology Proceedings, 2020)
This two-year study highlights the success of Bancakan Salak, a tourism event held in Galengdowo, to minimize the number of urbanization in Jombang. While modernization and globalization are all around the country-side, the threat of urbanization for rural areas is becoming significant and causes a slow-down. The event subsequently has been gradually changed the posture of Galengdowo’s population. Young people are more eager to live in their village now. This cultural tourism even became very helpful in empowering the lives in Galengdowo. Bancakan Salak had attracted many locals until international tourists come. By using the quantitative method and qualitative analysis, this study has hypothetically stated that Bancakan Salak could be even more successful because of the factor of its local champions. We are also articulating the concepts of glocalization and community-based tourism. Based on the research, we found that the government of the village plays a big role in shaping the situation. The head of the village and his secretary are examples of local champions. Their role signifies one part that is very crucial in building community-based tourism (CBT) which is leadership. This strong leadership is also built under the support of persistency, broader knowledge, and working networks.